Capturing Differential Allele-Level Expression and Genotypes of All Classical HLA Loci and Haplotypes by a New Capture RNA-Seq Method - Yamamoto, Fumiko; Suzuki, Shingo; Mizutani, Akiko; Shigenari, Atsuko; Ito, Sayaka; Kametani, Yoshie; Kato, Shunichi; Fernandez-Viña, Marcelo; Murata, Makoto; Morishima, Satoko; Morishima, Yasuo; Tanaka, Masafumi; et al. (Frontiers in Immunology, 2020)
The highly polymorphic human Major Histocompatibility Complex (MHC) also known as the HLA encodes class I and class II genes that are the cornerstone of the adaptive immune system. Their unique diversity (>25,000 alleles) might affect the outcome of any transplant, infection, and susceptibility to auto-immune diseases. The recent rapid development of new next generation sequencing (NGS) methods provides the opportunity to study the influence/correlation of this high level of HLA diversity on allele expression levels in health and disease. Here, we describe the NGS capture RNA-Seq method that we developed for genotyping all 12 classical HLA loci (HLA-A, HLA-B, HLA-C, HLA-DPA1, HLA-DPB1, HLA-DQA1, HLA-DQB1, HLA-DRA, HLA-DRB1, HLA-DRB3, HLA-DRB4 and HLA-DRB5) and assessing their allelic imbalance by quantifying their allele RNA levels. This is a target enrichment method where total RNA is converted to a sequencing-ready cDNA library and hybridized to a complex pool of RNA-specific HLA biotinylated oligonucleotide capture-probes, prior to NGS. This method was applied to 161 peripheral blood mononuclear cells and 48 umbilical cord blood cells of healthy donors. The differential allelic expression of 10 HLA loci (except for HLA-DRA and HLA-DPA1), showed strong significant differences (P < 2.1x10-15). The results were corroborated by independent methods. This newly developed NGS method could be applied to a wide range of biological and medical questions including graft rejections and HLA-related diseases.